UPAYA PERLINDUNGAN HUKUM BAGI PARA TENAGA KERJA INDONESIA (TKI) DI LUAR NEGERI DALAM PERSPEKTIF HUKUM INTERNASIONAL - I Gede Angga Aditya Putra; Ni Putu Rai Yuliartini (Jurnal Komunikasi Hukum, 2022)
Indonesia is a country that is still in the developing stage and that is also a problem for Indonesia itself due to the lack of human resources and the number of population numbers that continue to increase every year which results in the world of work sector, the lack of job vacancies in Indonesia has resulted in many citizens preferring to go abroad. to find work, they work as Indonesian workers. Indeed, working outside the country has many advantages such as the amount of wages earned. However, in reality there are still many problems regarding Indonesian workers, such as experiencing fraud by their departure agents, smuggling illegal workers, and when they are accepted to work there they receive inhumane treatment by their employers, such as physical violence or sexual violence. In these problems, it is necessary to take legal protection for Indonesian workers to prevent them from inappropriate actions, therefore the role of international law and national law is very much needed in overcoming these problems and cannot be separated from the role of the Indonesian government in protecting Indonesian workers who are abroad, and it should also be known what steps can be taken to protect Indonesian workers abroad.